Age- and sex-dependent increase in self-harm among adolescents with mental health problems in East China during COVID-19 related society-wide isolation - Liu, Wenjing; Hu, Zhishan; Liu, Zhen; Zhang, Fang; Ding, Yue; Shui, Ying; Yang, Zhi; Cheng, Wenhong (Frontiers in Public Health, 2023)
Objective The COVID-19 pandemic has raised concerns about child and adolescent mental health issues, such as self-harm. The impact of society-wide isolation on self-harming behaviors among adolescents in China is unclear. In addition, adolescents of different ages and sexes have varying abilities to cope with environmental changes. However, these differences are rarely considered in self-harm studies. We aimed to characterize the age- and sex-dependent effects of COVID-19-related society-wide isolation on self-harm among adolescents in East China. Methods We collected 63,877 medical records of children and adolescents aged 8–18 who had an initial visit to Shanghai Mental Health Center in China between 2017 and 2021 and charted annual self-harm rates for each age and sex. Using interrupted time series analysis, we modeled global and seasonal trends and the effect of COVID-19-related society-wide isolation on self-harm rates. Results Females aged 10–17 and males aged 13–16 exhibited significantly increasing trends in self-harm rate (pfdr < 0.05) in the past 5 years. Eleven-year-old females in 2020 showed a self-harm rate (37.30%) that exceeded the peak among all ages in 2019 (age 13, 36.38%). The COVID-19-related society-wide isolation elevated self-harm rates in female patients aged 12 [RR 1.45 (95% CI 1.19–1.77); pfdr = 0.0031] and 13 years [RR 1.33 (95% CI 1.15–1.5); pfdr = 0.0031], while males were less affected. Further, females with emotional disorders dominated the increased self-harm rates. Conclusion Society-wide isolation has had a significant impact on early adolescent females in East China, especially for those with emotional disturbances, and has brought forward the peak in adolescent self-harm rates. This study calls for attention to the risk of self-harm in early adolescents.